Evaluasi Website Forum United Indonesia dengan Metode Kansei Engineering dan Extended Goal Question Metric untuk Meningkatkan User Experience - Mochammad Aldi Kushendriawan; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
A community of forum service provider should fulfill the real needs of user and increase user's experience in supporting the community and forum sustainably. User experience can be measured by using User Experience Questionnaire (UEQ) calculation with six variables: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The aims of this study were: To analyze and redesign the user interface website of www.unitedindonesia.org/forum in order to increase user experience, to analyze user experience by using Kansei Engineering and Extended Goal Question Metrics, and to give some suggestions related to website design in order to fix user interface website of www.unitedindonesia.org/forum and increase the user experience. User experience is important in a website, and by analyzing the problems some suggestions can be recommended in order to maintain the old user and add more new user. Therefore, the forum can always be active. From the results, it was found that the implementation of user experience affect the user's behavior and emotions in their interaction with the website. Redesign of user interface in this thesis can increase the UX value. The highest improve of UX value are Novelty. While the highest positive impression from the old design to the new design is the â€œmodernâ€ item.